2014
DOI: 10.1007/s00381-014-2372-0
|View full text |Cite
|
Sign up to set email alerts
|

Retained medullary cord confirmed by intraoperative neurophysiological mapping

Abstract: Neurosurgical procedure for RMC should only be rendered with intraoperative neurophysiological mapping, as the anatomical judgment would not suffice to allow a safe cutting of these "normal-looking" neural structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Morphologically, there was a striking resemblance between the ependyma-lined canal with surrounding neuroglial tissues in our 6 patients with filar- and caudal-type lipomatous malformations and the RMC of the previous reports [8, 9], including ours [10, 11]. Furthermore, the cases were also similar to these previous cases in that there were always neuroglial tissues surrounded by variable amounts of collagenous and adipose tissues [8-11].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Morphologically, there was a striking resemblance between the ependyma-lined canal with surrounding neuroglial tissues in our 6 patients with filar- and caudal-type lipomatous malformations and the RMC of the previous reports [8, 9], including ours [10, 11]. Furthermore, the cases were also similar to these previous cases in that there were always neuroglial tissues surrounded by variable amounts of collagenous and adipose tissues [8-11].…”
Section: Discussionsupporting
confidence: 72%
“…During surgery for RMC, the exact border between the functional true conus and nonfunctional RMC is recommended by tracing the evoked CMAPs with direct cord stimulation starting from the functional portion of the cord, then on to the nonfunctional RMC [9, 10]. In our 6 cases, stimulation of the apparent lipomatous portion with a current intensity of up to 3 mA was strong enough to evoke CMAPs with stimulation of the ventral roots.…”
Section: Discussionmentioning
confidence: 99%
“…The key step in RMC surgery is to find the normal conus level based on electrophysiology. IONM enables identifying the normal function of the cord and root and severing the non-functioning RMC and vestigial root [15][16][17] .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…5). Sala et al 17) suggested rostrocaudal stimulation. This is a method to find the exact point when a signal becomes null.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation